Long-run impacts assessment of planned motorways and expressways in the Czech Republic - Milan Viturka; Vilém Paril; Petr Tonev (European Regional Science Association (ERSA), 2012)
In a large number of countries (including the Czech Republic), implementation of large projects of transport infrastructure is justified by a general reference to its broad economic benefits, which are, however, seldom further specified. One of important reasons for such an approach is the non-existence of an empirically verified model for complex assessment of the degree of necessity of the development of these projects. Therefore, the main objective of the paper is to present an original method for comparative assessment of motorway and expressway constructions. The method has been applied to eight cases of the most significant projects planned in the Czech Republic verifying that its use can provide the necessary information on their potential benefits (in spite of some simplifications). The methodology for the generalized assessment attempts to connect technical, economic, political, spatial and environmental aspects and includes five basic criteria: relevance (traffic intensity as the underlying factor determining the technical need for a project), usefulness (time saved in personal transport and haulage, due to the insecurity concerning future transport flows interpreted by relative values derived from design speeds), integration (strategic significance of the projects regarding the connection of the most significant residential areas and the connection with neighbouring countries), stimulation (economic impacts assessed based on a potential improvement of the factor of road and railway quality as an integral part of the regional quality of business environment), and sustainability (environmental impacts of the construction on more significant residential centres and selected protected areas, with emphasis on pollution and noise). The complex assessment of selected projects of motorways (D) and express ways (R) has been performed based on an aggregation of rankings of the projects within the defined criteria. The projects were then divided into three groups: projects where need for construction has been proven, has been found disputable or has not been proven. The first group contains R 55), D 3 and R 35. However, this does not mean that there are no drawbacks – e.g. R 35 has the lowest ranking within the sustainability criterion. The second group contains D 11 and R 49. The assessment of their construction has been negatively affected by their ranking within the usefulness and stimulation criteria (D 11), and relevance and integration criteria (R 49). The position of the projects in the third group, R 6, R 7 and R 43 follows from their bad ranking within most of the established criteria (R 6 and R 7 – three criteria; R 43 – all criteria except usefulness).
Keywords: 330